PERANAN SUTAN SJAHRIR DALAM USAHA MEMPERTAHANKAN KEMERDEKAAN INDONESIA (1945-1950) - Adika Wahyudi; Umi Hartati (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The problem in this research is the many obstacles that occur in the effort to maintain independence in Indonesia in 1945-1950. The purpose of this study is to analyze and describe the role of Sutan Sjahrir in Efforts to Maintain Indonesian Independence in the field of Politics. The research method uses historical research methods. Based on the results of the study, it can be concluded that Sjahrir is a combination of sharpness of knowledge and depth of mind. He is able to live in the tension between global and local. When Japan colonized Indonesia, Sjahrir had predicted that the Japanese would not last long in Indonesia. After two months of the Indonesian people gaining independence, Sjahrir felt that independence was only for the interests of the state, nation and also for political interests. The politics that Sjahrir wanted to implement was aimed more at prioritizing human freedom and the interests of society rather than national independence. Even though the Indonesian state has achieved independence, there are still things that are far more important, namely peace, prosperity, and progress for the people. Sutan Sjahrir is not just fighting for Indonesia's independence to be free from colonialism from other nations, but how to gain independence for small communities individually.